Sequential element control of non-precious dual atom catalysts on mesoporous carbon nanotubes for high performance lithium-oxygen batteries - Lim, Yeji; Chang, Hongjun; Kim, Huiju; Yoo, Yoon Jeong; Rho, YeoJin; Kim, Bo Ran; Byon, Hye Ryung; Moon, Janghyuk; Ryu, Won-Hee (Journal of materials chemistry. A, Materials for energy and sustainability, 2024)
Lithium-oxygen (Li-O 2 ) batteries, recognized as candidates for the highest energy storage, face challenges of irreversibility and low efficiency due to insulating discharge products. Addressing these issues, our study explores innovative dual-atom catalysts (DACs) comprising non-precious metals, specifically atomically scaled nickel (Ni) and iron (Fe), positioned on defective mesopore sites of nitrogen-doped carbon nanotubes (NCNTs) to enhance battery performance. We successfully achieved the synthesis of both homogeneous (Fe-Fe-NCNTs and Ni-Ni-NCNTs) and heterogeneous (Ni-Fe-NCNTs and Fe-Ni-NCNTs) DACs on NCNTs, by varying the loading sequences and combination of Ni and Fe. Our findings demonstrate that Fe-first-loaded DACs, particularly heterogeneous Ni-Fe-NCNT variants, excelled in both NO 2 − mediation reactivity and catalytic activity, achieving a longer lifespan of 200 cycles and maintaining consistent ORR/OER overpotential. Insights into the mesoporous loading sites and reaction mechanisms of these DACs in Li-O 2 cells were gained through density functional theory calculations. This research paves the way for replacing costly noble metal catalysts with tailored non-noble metal combinations, potentially revolutionizing Li-O 2 cell technology and broadening applications in heterogeneous catalysis. Introducing nickel and iron based homogeneous and heterogeneous dual atom catalysts (DACs) onto N-doped carbon nanotube defect sites significantly enhances Li-O 2 cell performance.